The effect of shear connectors on the strength, serviceability and dynamic response of composite floors using cold-formed steel beams and concrete in decking. (15th October 2022) - Cicione, Antonio; Walls, Richard
Highlights: Experimental testing, including dynamic response, and numerical modelling of cold-formed steel (CFS) composite beams. Shear connectors that prevent de-bonding between steel and concrete can significantly increase a composite beams bending capacity. Improving the shear interaction between the concrete and steel might slightly improve the dynamic behaviours of the floor. Additional failure mechanisms must be considered for such systems. Abstract: In recent years, the use of cold-formed steel sections in low-rise industrial and commercial building construction has increased significantly. Recent work has shown that composite action in floor systems consisting of cold-formed steel (CFS) sections is possible and that it can lead to substantial improvements in structural performance. However, limited guidelines have yet been established for composite systems comprising of CFS sections in order to allow the beneficial effect of composite action to be exploited. The aim of this study is to (a) investigate the effect of different shear connectors on the static and dynamic behaviour of composite action in floors comprising of CFS beams and (b) to investigate if conventional guidelines (such as SANS 10162-1/CSA S16) for hot-rolled composite beams can be applied to composite systems comprising of CFS sections. This paper presents an experimental study of five identical full-scale composite floors, but with different shear connectors, under four-point loading. Additionally, vibration tests were conducted for each floor, and natural frequencies were obtained. The proportion of shear connectivity was varied between 0 and 100 % in the experiments, in addition to considering a plate to link connectors into the concrete flange. It was found that if adequate shear connection is provided, composite action can reliably be achieved in composite systems comprising of CFS sections. Furthermore, all floors had a first natural frequency larger than 10.2 Hz, which was assumed to be the lower limit for a system to not be susceptible to resonance. The results indicated that the shear connectors have a substantial effect on the ultimate limit state behaviour and that it may improve vibration response, although further work is needed.